63.1k views
5 votes
Helpppppppppp aasapppp

Helpppppppppp aasapppp-example-1

2 Answers

3 votes

Answer:

2

Explanation:

Simplify the following:

(-(2 + 2/3))/(-(1 + 1/3))

(-(2 + 2/3))/(-(1 + 1/3)) = (-1)/(-1)×(2 + 2/3)/(1 + 1/3) = (2 + 2/3)/(1 + 1/3):

(2 + 2/3)/(1 + 1/3)

Put 1 + 1/3 over the common denominator 3. 1 + 1/3 = 3/3 + 1/3:

(2 + 2/3)/(3/3 + 1/3)

3/3 + 1/3 = (3 + 1)/3:

(2 + 2/3)/((3 + 1)/3)

3 + 1 = 4:

(2 + 2/3)/(4/3)

Put 2 + 2/3 over the common denominator 3. 2 + 2/3 = (3×2)/3 + 2/3:

((3×2)/3 + 2/3)/(4/3)

3×2 = 6:

(6/3 + 2/3)/(4/3)

6/3 + 2/3 = (6 + 2)/3:

((6 + 2)/3)/(4/3)

6 + 2 = 8:

(8/3)/(4/3)

Multiply the numerator by the reciprocal of the denominator, (8/3)/(4/3) = 8/3×3/4:

(8×3)/(3×4)

(8×3)/(3×4) = 3/3×8/4 = 8/4:

8/4

The gcd of 8 and 4 is 4, so 8/4 = (4×2)/(4×1) = 4/4×2 = 2:

Answer: 2

User Chris Kobrzak
by
4.5k points
1 vote

Answer:

2

Explanation:

Convert mixed fraction to improper fraction


-2(2)/(3)=-(8)/(3)\\\\\\-1(1)/(3)=-(4)/(3)


-2(2)/(3) ÷
-1(1)/(3) =
(-8)/(3) ÷
-(4)/(3)


=-(8)/(3)*-(3)/(4)\\\\\\=2 *1 \\\\= 2

User Wemu
by
5.8k points